Joint exploration of network pharmacology and metabolomics on the effects of traditional Chinese medicine compounds in weaned yaks - Lu, Sijia; Zhu, Yanbin; Zhang, Xiaojuan; Cidan, Yangji; Basang, Wangdui; Li, Kun (Frontiers in Veterinary Science, 2025)
IntroductionChinese herbal medicines are relatively inexpensive and have fewer side effects, making them an effective option for improving health and treating diseases. As a result, they have gained more attention in recent years. The weaning period is a critical stage in the life of yaks, often inducing stress in calves. Weaning stress, along with dietary changes, can lead to a decline in physical fitness and immune function, making yaks more susceptible to diarrhea and resulting in high mortality rates during this period. Therefore, our study aimed to address this issue by incorporating traditional Chinese medicine (TCM) formulas into the diet of yaks during the weaning period.MethodsFollowing a dialectical analysis, three TCM formulas, mainly composed of Paeonia lactiflora, Coptis chinensis, and Dandelion, were identified for their anti-inflammatory, antioxidant, and immune enhancing potentials. We explored the possible molecular mechanisms of these TCM formulas using network pharmacology analysis and investigated their effects on the physiology of yaks through metabolomics.ResultsNetwork pharmacology analysis revealed several key target proteins in the protein–protein interaction (PPI) network between three formulas and immune-related genes, including PIK3R1, PIK3CA, JAK2, PTK2, and PYPN11. The key target proteins in the PPI network associated with metabolism-related genes included ENPP1, CYP1A1, PTGS1, members of the CYP1 family, and EPHX2. GO analysis of co-targets revealed highly enriched pathways such as protein phosphorylation, plasma membrane, and one-carbon metabolic processes. Metabolomics revealed significant changes in the abundance of metabolites including dimethyl sulfoxide, tyrphostin A25, and thromboxane A2 in the intestines of weaned yaks supplemented with these Chinese herbal compounds. Significant changes were also observed in pathways such as vitamin A metabolism, chloroalkane, and chloroalkene degradation.DiscussionBased on these findings, it can be inferred that TCM formulas improve the physical fitness of weaned yaks by enhancing antioxidant capacity, boosting immunity, and reducing intestinal inflammation. This study preliminarily elucidates the pharmacological mechanisms by which TCM formulas prevent diarrhea and improve physical fitness in weaned yaks through metabolomics and network pharmacology, paving the way for further evaluation of the effectiveness of these three formulas.